2023
DOI: 10.1186/s42836-023-00199-y
|View full text |Cite
|
Sign up to set email alerts
|

Joint aspiration for diagnosis of chronic periprosthetic joint infection: when, how, and what tests?

Nicole Durig Quinlan,
Jason M. Jennings

Abstract: Diagnosing chronic periprosthetic joint infection (PJI) requires clinical suspicion in combination with both serological and synovial fluid tests, the results of which are generally applied to validated scoring systems or consensus definitions for PJI. As no single “gold standard” test exists, the diagnosis becomes challenging, especially in the setting of negative cultures or equivocal test results. This review aims to address the workup of chronic PJI and considerations for clinical evaluation to guide treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Barrack et al analyzed 78 cases of aspiration in order to detect PJI after TKA and showed a sensitivity of 65.4% and a specificity of 96.1% [23]. By performing several tests simultaneously (C-reactive serum level, leukocyte in serum culturing, leukocyte count in the aspirate, alpha-defensin determination), a very high accuracy can be achieved [24].…”
Section: Discussionmentioning
confidence: 99%
“…Barrack et al analyzed 78 cases of aspiration in order to detect PJI after TKA and showed a sensitivity of 65.4% and a specificity of 96.1% [23]. By performing several tests simultaneously (C-reactive serum level, leukocyte in serum culturing, leukocyte count in the aspirate, alpha-defensin determination), a very high accuracy can be achieved [24].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic algorithm used in this retrospective study has been elaborated according to the SA/PJI diagnostic criteria as presented by the 2018 International Consensus Meeting for Periprosthetic Joint Infections [ 25 ] and the European Bone and Joint Infection Society [ 17 ]. The algorithm has been completed by the implementation of modern, synovial fluid molecular testing technologies that have been recently recommended by multiple authors [ 5 , 12 , 22 , 23 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Unlike serology, joint fluid detection is distinct as serum markers can be influenced by acute or chronic inflammatory diseases in various organs and systems of the body, whereas inflammatory analysis of joint fluid, owing to its limited fluidity and containment within the joint capsule, offers a truer reflection of the local inflammatory condition ( Figure 1C ). 29 Preoperative synovial fluid aspiration in patients with suspected infections allows for the detection of leukocyte count and polymorphonuclear cell percentage, as well as pathogen culture. 30 , 31 This improves diagnostic accuracy and provides essential information for formulating targeted treatment plans.…”
Section: Diagnosismentioning
confidence: 99%